Incorporation of Ba2+ ions on the properties of MoO3 thin films and fabrication of positive photo-response Cu/Ba–MoO3/p-Si structured diodes. (September 2019) - Vivek, P.; Chandrasekaran, J.; Marnadu, R.; Maruthamuthu, S.; Balasubramani, V.
Abstract: Metal-insulator-semiconductor (MIS) structured Schottky barrier diodes (SBDs) are the most significant device in optoelectronic device application. Here, we demonstrated a highly rectifying SBDs using a thin interfacial layer among p-type silicon (p-Si) and metal (Cu) junction. These composite films are coated with different concentrations of Ba (0, 5, 10 and 15 wt%) using jet nebulizer spray pyrolysis (JNSP) technique with an optimized substrate temperature of 500 °C. A significant reduction of reverse saturation (Io) current was obtained on introducing the Ba–MoO3 composite films in between Cu/p-Si interface. X-ray diffraction (XRD) pattern revealed the monoclinic crystalline phases of Ba–MoO3 thin films along with improved grain size. Field emission scanning electron microscope (FE-SEM) images of the prepared thin films displayed a plate-like structure, which on increasing the Ba concentration transforms into a flag-like structure. The presence of constituent elements like O, Mo, Ba were confirmed by energy dispersive analysis X-Ray (EDAX) spectrum. The atomic force microscopy (AFM), exposed a smoother surface and an improved surface roughness of the film while varying the Ba concentration. Band gap energy of the Ba–MoO3 films are found to increase after adding the Ba content. The electrical conductivity decreased with increasing Ba concentration of Ba–MoO3 films corresponding activation energy is increased. All the fabricated Cu/Ba–MoO3 /p-Si diodes show positive photoconducting nature, in which the ideality factor of the diode decreases gradually with Ba concentration. Hence 15 wt% of Ba shows better device performance relatively with other diodes. Graphical abstract: Image 1 Highlights: Highly rectifying Cu/Ba–MoO3 /p-Si structured Schottky barrier diodes has been fabricated through low cost jet nebulizer spray pyrolysis technique. The phase changes was observed (orthorombic to monoclinic) while increasing Ba concentration. Remarkably, the plate-like and flower-like sufface morphology was revealed by FE-SEM. Cu/Ba–MoO3 /p-Si diode fabricated with 15 exposes a lower n = 1.92 values under light condition. The Cu/Ba–MoO3 /p-Si diodes highly appropriate for UV photodetector application.